1988
DOI: 10.1007/bf01872326
|View full text |Cite
|
Sign up to set email alerts
|

Very low osmotic water permeability and membrane fluidity in isolated toad bladder granules

Abstract: Osmotic water permeability of the apical membrane of toad urinary epithelium is increased greatly by vasopressin (VP) and is associated with exocytic addition of granules and aggrephores at the apical surface. To determine the physiological role of granule exocytosis, we measured the osmotic water permeability and membrane fluidity of isolated granules, surface membranes and microsomes prepared from toad bladder in the presence and absence of VP. Pf was measured by stopped-flow light scattering and membrane fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…This value is also notably higher than the Pr reported for membranes known to contain water channels including human erythrocytes (0.02 cm/s; Macey, 1984), proximal tubule apical and basolateral membranes (0.01-0.03 cm/s; Meyer and Verkman, 1987), and vasopressin-induced endosomes from rat kidney papilla (0.03 cm/s; . In toad bladder granules, which fuse, together with aggrephores, with the mucosal membrane in response to vasopressin stimulation (Masur et al, 1986), Pf was reported to be 0.0005 cm/s at 23~ (Verkman and Masur, 1988). The high Pf in toad bladder endocytic vesicles therefore constitutes strong evidence in itself for the presence of functional water channels.…”
Section: Discussionmentioning
confidence: 97%
“…This value is also notably higher than the Pr reported for membranes known to contain water channels including human erythrocytes (0.02 cm/s; Macey, 1984), proximal tubule apical and basolateral membranes (0.01-0.03 cm/s; Meyer and Verkman, 1987), and vasopressin-induced endosomes from rat kidney papilla (0.03 cm/s; . In toad bladder granules, which fuse, together with aggrephores, with the mucosal membrane in response to vasopressin stimulation (Masur et al, 1986), Pf was reported to be 0.0005 cm/s at 23~ (Verkman and Masur, 1988). The high Pf in toad bladder endocytic vesicles therefore constitutes strong evidence in itself for the presence of functional water channels.…”
Section: Discussionmentioning
confidence: 97%
“…Such a drop in P,, (or Lp) with increasing osmotic gradient has been observed in charophytes (Dainty and Ginzburg, 1964;Kiyosawa and Tazawa, 1972;Steudle and Tyerman, 1983) and was previously interpreted as a "dehydration effect" on membrane pores (Dainty and Ginzburg, 1964). In animal systems both dependence of P,, on osmotic gradient (Illsley and Verkman, 1986;Verkman et al, 1989;Jansson and Illsley, 1993) and independence thereof (Meyer and Verkman, 1986;Verkman and Masur, 1988) have been described. The decline in P,, that we observed in the tonoplast-enriched lower phase might well be a physiological closing-down response of water channels to a presumed water deficit.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of diffusion is therefore dependent on the thickness of the membrane, the length, saturation, and packing of the acyl chains, and the molecular volume and hydrophobicity of the solute (Walter and Gutknecht, 1986;Finkelstein, 1987;Disalvo, 1988;Paula et al, 1996). As predicted by this model, fluidity appears to be a major determinant in the rate of permeation of nonelectrolytes across lipid membranes (Worman et al, 1986;Verkman and Masur, 1988;Giocondi and Le Grimellec, 1991;Lande et al, 1995). Indeed, there is compelling experimental evidence to suggest that reducing membrane fluidity is an important means by which epithelial cells can erect barriers to permeation.…”
Section: Introductionmentioning
confidence: 96%